PENGELOLAAN POJOK BACA SEBAGAI UPAYA MEMBANGUN KARAKTER ANAK DI RT 006/RW 18 KELURAHAN SUNGAI BANGKONG PONTIANAK KOTA - Tuti Kurniati (Jurnal Buletin Al-Ribaath, 2018)
ABSTRACTThe reading interest of Indonesian children is in the category of concern. There many factors the cause of low children's interest in reading, from economic factors to environmental factors. RT 06 / RW 08, the Bangkong River Village is one of the areas in the city of Pontianak that needs to be improved the reading interest. In this environment still do not have the facilities and infrastructure that can facilitate school-age children to gain knowledge through reading activities. Even if the child's interest in reading has been stimulated from an early age, it can build morals and morals in children. Therefore, through this dedication the dedication team made a reading corner as a vehicle to foster interest in reading for children which not only contained reading books, but was able to facilitate children in growing and developing their character with non-book items, such as crayons, picture books, colored pencils, colored papers and other craft objects. The purpose of this service activity is to provide supporting facilities in the form of elementary school textbooks and other science books as well as providing non-book items to develop children's creativity and children's positive imagination.  Keywords : character, desire of reading, reading home